Veterinary nursing in the United Kingdom: Identifying the factors that influence retention within the profession - Jeffery, Andrea; Taylor, Eleanor (Frontiers in Veterinary Science, 2022)
Abstract The UK regulatory body for Registered Veterinary Nurses (RVNs), the Royal College of Veterinary Surgeons (RCVS), maintains the professional register of RVNs. Every year a proportion fail to re-join the register. This research identified the factors which predict retention and presented a set of recommendations to inform the Royal College of Veterinary Surgeons as the regulator and the veterinary professions as a whole. A secondary analysis of the raw quantitative data generated by the 2014 and 2019 RCVS Surveys of the Veterinary Nurse Profession was undertaken using multivariate logistic regression analysis. Quantitative analysis found significant relationships between intention to leave and the following factors in both the 2014 and 2019 survey data: job satisfaction; believing that veterinary nursing offers good opportunities for career progression; satisfaction with employer support and having a second job. The following factors were significant in 2014 but not in 2019: undertaking nurse clinics; feeling valued and being respected by veterinary surgeons. The 2014 survey included a single question about respect shown by employers/veterinary surgeons. In the 2019 survey this question was separated into two separate questions. Therefore, we cannot draw conclusions from the differing results from 2014 and 2019. In relation to client expectations representing a main challenge for respondents, however, this was not significant in 2014 but had gained significance in 2019. The factors that influence the retention of nurses within the profession are multifactorial and individual. Nurses are responsible for ensuring that those they work with are aware of their skill set and that they themselves are accountable for utilisation of those skills. When veterinary nurses are supported by their employers, they are more likely to stay in the profession. Having a clearly defined career structure and mapped progression routes will be helpful. A sense of job satisfaction was another important factor in retention. A pay structure linked to a career pathway framework, such as in human centered nursing, is an area for further work.